FOOD INTOLERANCE - Jandric-Kocic, Marijana (HEALTH CARE, 2022)
Food intolerance is a non-immunological response induced by a food or food component in a dose that is normally tolerated. It includes pseudoallergic and pharmacological effects caused by: salicylates, biogenic amines, sulfites, sodium glutamate, colors and preservatives, sweeteners, or enzymopathies. The pathophysiology, clinical manifestations, diagnosis and treatment of the most common food intolerances have been presented in this review article. The literature search was done with the help of the following keywords: intolerance, food, additives, carbohydrates and gluten within PubMed, Embase, Scopus, SCIndeks and Hrčak databases. According to the literature, it may be argued that the lack of standardized tests accounts for the discrepancy between the perceived prevalence of food-related adverse effects, which are extremely common, and the actual prevalence of non-immunological reactions to food within these events. Food intolerance is manifested primarily by gastrointestinal and then extraintestinal (neurological, cardiovascular, respiratory and dermatological) signs and symptoms. Diagnosis requires a detailed medical history, physical examination, as well as keeping a diet and symptom diary, implementing an elimination diet and double-blind placebo-controlled oral food exposure tests. Treatment includes dietary modification, supplementation and treatment of the underlying condition in persons with secondary intolerance.